Efficiency Analysis of Foundation System - Resi Aseanto; Ali Ramdani Bagaskara; Syafwandi; Agung Sumarno (Neutron, 2022)
The increasing number of residents in South Tangerang has an impact on increasing the need for lower housing. The development of vertical housing with the market name of flats, apartments and is the most effective anticipatory solution to overcome land prices which result in market limitations, especially for the upper middle class. This 32-storey apartment project uses a combined foundation system between drill pile foundation & raft foundation. With the combination of these two very massive systems, of course, it will have a very expensive cost to implement and take a long time to complete. In order to avoid cost overruns, the foundation design must look at the possibilities. To determine the efficiency of the combined system foundation design between pile bored foundation & raft foundation, the researchers analyzed the value of the bearing capacity and also the settlement that occurred in the existing foundation using the Poulos method, the equivalent Raft method and the Vesic method. From the results of the study, it was found that the contribution of the pile foundation bearing capacity was 24.10%. the placement of the raft foundation is 75.90% and the settlement analysis using the Poulos 8.95cm method, the 12.41cm Equivalent Raft method and the Vesic 12.1cm method, these three results are close to the maximum settlement limit.